2021
DOI: 10.3889/oamjms.2021.5638
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Educational Intervention on Knowledge and Attitudes toward Sexually Transmitted Infections on a Sample of Egyptian Women at Primary Care Level

Abstract: OBJECTIVES: The current study was conducted to assess the effect of an educational intervention on knowledge status and attitudes toward sexually transmitted infections (STIs) in a sample of women in reproductive age. METHODS: One group quasi-experimental study was conducted at one primary health care center in Egypt; included 200 women selected by systematic sampling method. Health education intervention was designed and implemented to fill the knowledge gap revealed in pre-test in relation to preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(18 reference statements)
3
0
0
Order By: Relevance
“…This finding agreed with [19], who stated that significant group differences were found at different times (pre and post mobile-based educational program) in STD knowledge. In the same line this study finding agreed with [20], who showed that there significant improvement of the women total knowledge level from the pre-intervention to in the post-test (p = 0.001). This might be connected to the epidemiological triangle model, which assists in increasing women's education and encourage a clear understanding of STDs.…”
Section: Discussionsupporting
confidence: 91%
“…This finding agreed with [19], who stated that significant group differences were found at different times (pre and post mobile-based educational program) in STD knowledge. In the same line this study finding agreed with [20], who showed that there significant improvement of the women total knowledge level from the pre-intervention to in the post-test (p = 0.001). This might be connected to the epidemiological triangle model, which assists in increasing women's education and encourage a clear understanding of STDs.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding total knowledge, the satisfactory level of the total knowledge scores was increased from 34% in the pre-test to 86% in the post-test. This improvement was maintained during the follow-up assessment, with 77.3% of participants still demonstrating a satisfactory level of knowledge with statistically significant differences (P<0.001) these results were in agreement with several previous studies (Abera et al, 2022;Amin et al, 2021;Alkalash et al, 2020;Kazemi et al, 2022;Sonawane & G Mendagudli, 2020;Rosyda et al, 2019)…”
Section: Concerningsupporting
confidence: 92%
“…Results of the current study revealed that, most of the studied women had unsatisfactory level of total knowledge score in the pretest. This finding is supported by many recent Egyptian studies (Aziz et al, 2022;Ahmed, 2022;Amin et al, 2021;Mohamed et al, 2021). The limited knowledge about cervical cancer prior to the intervention in this study can partly be attributed to the lack of a national strategy for executing outreach and educational initiatives aimed at the general populace, particularly women of reproductive age.…”
Section: Discussionsupporting
confidence: 67%